Goldberg-Shprintzen Syndrome & Cerebral Dysgenesis - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1994)
A 5-year-old girl with Goldberg-Shprintzen syndrome and an abnormal CT scan suggesting neuronal migration defect or brain dysgenesis is reported from the Departments of Pediatrics, Asahikawa Habilitation Center, and Kitami Red Cross Hospital, Japan.